Distinguishing Chain Growth Mechanisms in Metal-catalyzed Olefin Oligomerization and Polymerization Systems: C2H4/C2D4 Co-oligomerization/Polymerization Experiments Using Chromium, Iron, and Cobalt Catalysts. - Tomov,AK; Gibson,VC; Britovsek,GJP; Long,RJ; van,Meurs M; Jones,DJ; Tellmann,KP; Chirinos,JJ (Organometallics, 2009)
A series of co-oligomerization and copolymn. reactions of C2H4/C2D4 (1:1) mixts. have been carried out using various transition metal catalysts based on Cr, Co, and Fe in combination with MAO. The oligomeric α-olefin products have been analyzed by GC and GC/MS, and the exptl. results have been compared with the theor. mass spectra derived from math. models. Solid polymer samples have been analyzed by 13C{1H} and 13C DEPT-135 NMR spectroscopy. C2H4/C2D4 co-oligomerization can be used as a method to differentiate between a metallacyclic or a Cossee-type chain growth mechanism in oligomerization systems. In the case of a metallacyclic mechanism, no H/D scrambling is obsd., whereas for a Cossee-type mechanism, similar rates of chain propagation and chain termination (β-H elimination) result in rapid H/D scrambling of the C2H4/C2D4 feed. This method is therefore limited to oligomerization systems and cannot be applied in polymn. systems, where the rate of chain propagation is much faster than the rate of chain termination. [on SciFinder(R)]